1995
DOI: 10.1007/bf01213322
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for survival in patients with advanced renal cell carcinoma treated with interleukin-2 and interferon-?

Abstract: A group of 73 patients with advanced renal cell carcinoma, treated in different phase II trials with interferon alpha and/or interleukin-2, have been evaluated to identify potential baseline prognostic factors predicting their survival. The eligibility criteria were very similar across studies and included ECOG performance status < or = 2, measurable or evaluable disease and no CNS metastases. The overall response rate was 8%. The overall survival was 33% at 2 years and 18% at 1 year. In the univariate analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…A related possibility is that older patients may tend to have a less aggressive pattern of disease [94], and hence have a more favorable prognosis. Previous studies of prognosis of RCCa have not shown any trend towards longer survival among older patients with advanced disease [6, 7, 8, 9, 10, 11], and several studies have suggested a worse prognosis among older patients [95, 96, 97]. We found that studies with larger numbers of older patients (higher median ages) had shorter median survivals (table 3).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…A related possibility is that older patients may tend to have a less aggressive pattern of disease [94], and hence have a more favorable prognosis. Previous studies of prognosis of RCCa have not shown any trend towards longer survival among older patients with advanced disease [6, 7, 8, 9, 10, 11], and several studies have suggested a worse prognosis among older patients [95, 96, 97]. We found that studies with larger numbers of older patients (higher median ages) had shorter median survivals (table 3).…”
Section: Discussionsupporting
confidence: 61%
“…Although there have been many excellent analyses of RCCa prognostic factors, these have generally focused upon survival rather than response [6, 7, 8, 9, 10, 11]. In this analysis, we were able to draw upon a larger sample of responding patients than has been previously practical.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The features that were associated with survival in a multivariate analysis included Eastern Cooperative Oncology Group performance status (0 to 1 versus 2 to 3), time from initial diagnosis (Ͼ1 year versus Յ1 year), number of metastatic sites, prior cytotoxic chemotherapy, and recent weight loss. Additional analyses have appeared recently, and multiple reports analyzing prognostic factors in patients with metastatic renal cell carcinoma have been published (15)(16)(17)(18)(19)(20)(21)(22). In these reports, no factor independently predicted survival.…”
Section: Introductionmentioning
confidence: 99%
“…A more consistent finding is the value of the total number of metastatic sites involved, which serves as a crude estimate of overall tumor burden [4,29,31,34,35]. The relative risk (RR) of mortality was increased two-to fourfold when more than a single metastatic site was involved [29,31,35]. The time interval between initial diagnosis and metastasis is a significant determinant of prognosis.…”
Section: Prognostic Indicators Of Renal Cell Carcinomamentioning
confidence: 92%